The Effect of Capital Structure, Business Risk, and Asset Structure on Financial Performance: An Empirical Study of Automotive Companies Listed on the Indonesia Stock Exchange for the 2019–2023 Period - Irmayanti Irmayanti; Yudi Nur Supriadi; Etty Nurwati; Sri Purwanto; Moeljadi Moeljadi (Dinasti Publisher, 2025)
This study aims to analyze the effect of capital structure (Debt-to-Equity Ratio/DER), business risk (Beta), and asset structure (Current Asset to Total Asset Ratio/CATA) on the financial performance (Return on Assets/ROA) of automotive companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employs a quantitative approach utilizing secondary data. The population consists of all automotive companies listed on the Indonesia Stock Exchange from 2019 to 2023, with purposive sampling used to select the sample. The study applies Descriptive Statistical Analysis, Classical Assumption Tests, Multiple Linear Regression Analysis, t-test, F-test, and the Coefficient of Determination (R²). The results show that Beta and CATA have a positive and significant effect on the ROA of automotive companies in Indonesia, while DER does not have a significant effect. Simultaneously, the three independent variables (DER, Beta, and CATA) have a significant effect on ROA, with an Adjusted R² of 86.23%, reflecting the model's ability to explain the variability in financial performance. This study is original as it integrates the analysis of capital structure, business risk, and asset structure to provide a comprehensive assessment of financial performance in the automotive sector, while also updating the analysis period through 2023.